MYC/MIZ1-dependent gene repression inversely coordinates the circadian clock with cell cycle and proliferation - Shostak, Anton; Ruppert, Bianca; Ha, Nati; Bruns, Philipp; Toprak, Umut; Eils, Roland; Schlesner, Matthias; Diernfellner, Axel; Brunner, Michael (Nature Communications, 2016)
The circadian clock and the cell cycle systems coordinate global physiology. Here the authors show that MYC represses the clock genes, together with MIZ1, and induces proliferation, suggesting that MYC inversely modulates cell cycle and circadian clock genes.